2022
DOI: 10.1038/s43705-022-00196-3
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome diversity and metabolic capacity determines the trophic ecology of the holobiont in Caribbean sponges

Abstract: Sponges are increasingly recognized as an ecologically important taxon on coral reefs, representing significant biomass and biodiversity where sponges have replaced scleractinian corals. Most sponge species can be divided into two symbiotic states based on symbiont community structure and abundance (i.e., the microbiome), and are characterized as high microbial abundance (HMA) or low microbial abundance (LMA) sponges. Across the Caribbean, sponge species of the HMA or LMA symbiotic states differ in metabolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…LMA symbiotic state is the ancestral state among sponges, while HMA symbioses, consisting of higher specialized microbes, have evolved numerous times through the recruitment of similar assemblages. Furthermore, recent studies have found that HMA holobionts have higher endemism and metabolic dependence and encode for secondary-metabolite biosynthesis in chemical defenses [ 88 , 89 ].…”
Section: Chemical Ecology-driven Discovery Of Marine Medicinesmentioning
confidence: 99%
“…LMA symbiotic state is the ancestral state among sponges, while HMA symbioses, consisting of higher specialized microbes, have evolved numerous times through the recruitment of similar assemblages. Furthermore, recent studies have found that HMA holobionts have higher endemism and metabolic dependence and encode for secondary-metabolite biosynthesis in chemical defenses [ 88 , 89 ].…”
Section: Chemical Ecology-driven Discovery Of Marine Medicinesmentioning
confidence: 99%
“…Sponges are sessile, filter‐feeding animals that typically harbour species‐specific, temporally stable and diverse symbiotic microbiomes (Easson & Thacker, 2014; Erwin et al., 2015; Lesser et al., 2022; Pita et al., 2013; Schmitt et al., 2012; Taylor et al., 2007; Thomas et al., 2016). Symbiont communities co‐diversify with host lineages, which often rely on symbionts for both nutrition and chemical protection against predation (Lesser & Slattery, 2013; Pankey et al., 2022; Pawlik, 2011; Slaby et al., 2017; Taylor et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Symbiont communities co‐diversify with host lineages, which often rely on symbionts for both nutrition and chemical protection against predation (Lesser & Slattery, 2013; Pankey et al., 2022; Pawlik, 2011; Slaby et al., 2017; Taylor et al., 2007). Together, sponges and their symbionts serve valuable ecological and biogeochemical roles in coral reef ecosystems through benthic–pelagic coupling and nutrient cycling (Freeman et al., 2020; Lesser, 2006; Lesser et al., 2018, 2022; Webster & Taylor, 2012; Wulff, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sponges, both high and low microbial abundance symbiotic states, known as HMA and LMA phenotypes, respectively, in the sponge biology literature (Hentschel et al 2006), also consume DOM with the rates of uptake and assimilation greater in high microbial abundance sponges compared to low microbial abundance sponges (Hoer et al 2018; McMurray et al 2018). Rates of pumping, choanocyte chamber densities and POM uptake and assimilation, however, are commonly higher in low microbial abundance sponges when assessed directly or when using stable isotopic analyses (Weisz et al 2008; Maldonado et al 2012; Poppell et al 2014; McMurray et al 2018; Rix et al 2020; Macartney et al 2021 a , b , 2022; Lesser et al 2022) with some low microbial abundance sponge species apparently not utilizing DOM at all (de Goeij et al 2017; Hoer et al 2018; McMurray et al 2018). In high microbial abundance sponges the majority of DOM uptake is driven by their microbiomes as host DOM uptake is equivalent between high microbial abundance and low microbial abundance sponges (Rix et al 2020).…”
mentioning
confidence: 99%